A LITERATURE REVIEW ON MITIGATION STRATEGIES FOR ELECTRICAL COMPONENT OBSOLESCENCE IN MILITARY-BASED SYSTEMS - Rust, Ryan Marcel; Elshennawy, Ahmad; Rabelo, Luis (The South African Journal of Industrial Engineering, 2022)
The aim of this research is to conduct an all-inclusive investigation on past studies of obsolescence, the issues involved, and tactics for mitigation in military-based systems. This research investigates four categories: 1. Obsolescence Consequences, 2. Life Cycle Stages and Strategies for Life Cycle Management, 3. Design for Obsolescence and Cost Optimisation, and 4. Management and Tools. A quantitative approach was used to determine the key topics of the 55 articles used in this literature review. A keyword and topic matrix was used to determine the six main areas of concern in current research, and then broken down further into the four categories discussed in this paper. A deep dive into the literature shows that the main areas of concern for obsolescence are cost optimisation, obsolescence management, system life cycle, design/system refresh planning, architecture/open systems, and end-of-life (EOL) predictions. In the EOL predictions category, only one article proposed the idea of machine learning as a forecasting method. This effort suggests a need for a more streamlined management approach to tackling obsolescence. Newer research shows an interest shift from system life cycle management towards forecasting techniques and looking towards future proactive management improvements. This study demonstrates opportunities and challenges for entities dealing with component obsolescence and methods for minimising the issues that go along with it. This paper identifies current practices for obsolescence management, and points to areas for further research development.